2017
DOI: 10.1161/hypertensionaha.117.09512
|View full text |Cite
|
Sign up to set email alerts
|

Perivascular Adipose Tissue Angiotensin II Type 1 Receptor Promotes Vascular Inflammation and Aneurysm Formation

Abstract: Perivascular adipose tissue exhibits characteristics of active local inflammation, which contributes to the development of atherosclerotic disease as a complication of obesity/metabolic syndrome. However, the precise role of perivascular adipose tissue in the progression of abdominal aortic aneurysm remains unclear. To test the hypothesis that genetic deletion of angiotensin II type 1a (AT) receptor in perivascular visceral adipose tissue (VAT) can attenuate aortic aneurysm formation in apolipoprotein E-defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 47 publications
1
42
0
1
Order By: Relevance
“…In addition, the role of perivascular visceral adipose tissue AT 1A R contributing to ANG II-induced AAA has been reported. Adipocyte-derived osteopontin via AT 1A R stimulation appears to contribute to AAA through inflammatory actions involving macrophage migration and polarization (902). Taken together, these studies highlight the roles of distinct cell type-specific signaling mechanisms by which ANG II may contribute to AAA development and the need for further investigation.…”
Section: Cell Type Specific Signaling Mechanisms Leading To Aaamentioning
confidence: 81%
“…In addition, the role of perivascular visceral adipose tissue AT 1A R contributing to ANG II-induced AAA has been reported. Adipocyte-derived osteopontin via AT 1A R stimulation appears to contribute to AAA through inflammatory actions involving macrophage migration and polarization (902). Taken together, these studies highlight the roles of distinct cell type-specific signaling mechanisms by which ANG II may contribute to AAA development and the need for further investigation.…”
Section: Cell Type Specific Signaling Mechanisms Leading To Aaamentioning
confidence: 81%
“…The AT1R is responsible for most biological effects of Ang II such as pressure, trophic, and pro-inflammatory effects. Sakaue et al reported that ATR1 receptor in PVAT promotes vascular inflammation and aneurysm formation [ 268 ]. Previous research has reported angiotensin receptor blockers (ARBs) and angiotensin converting enzyme inhibitors (ACEI) reduced PVAT inflammation, which is associated with the reduction of atherogenesis [ 269 ].…”
Section: Therapeutic Targeting On Pvatmentioning
confidence: 99%
“…Perivascular adipose tissue (PVAT) is a structure surrounding most of the blood vessels, which plays vital roles in vascular physiopathology ( Brown et al, 2014 ). As an essential part of the vasculature, PVAT is involved in various vascular diseases, including atherosclerosis, aneurysm, and hypertension ( Takemori et al, 2007 ; Verhagen and Visseren, 2011 ; Sakaue et al, 2017 ). It is well established that adipose tissue includes brown adipose tissue (BAT) and white adipose tissue (WAT).…”
Section: Introductionmentioning
confidence: 99%